Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gamification on Users Knowledge-Sharing Practices: Relationships between Work Motivation, Performance Expectancy and Work Engagement

Abstract: How to engage and motivate employees to share their knowledge has become one of the main organizational strategic goals. This study, supported by the Flow theory and Kahn's theory of engagement, investigated how the impact of gamification on user's knowledge-sharing practices. We ran an online survey of 147 participants from a large organization that implemented social engagement and motivational systems to leverage internal knowledgesharing practices. Our study revealed important drivers of job motivation (en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…In contrast, if a person has a low motivation, he or she will not strive for the work so that it ends up with a low working output. This fact is supported by several studies, which suggested that training and motivation would affect the improvement of employee performances, as in research by [5], [15], [17], [20], [24], [32], [36] . Based on the study upon prior research, either conceptually or empirically, a hypothesis was proposed as follows:…”
Section: The Effect Of Motivation On Performancementioning
confidence: 63%
“…In contrast, if a person has a low motivation, he or she will not strive for the work so that it ends up with a low working output. This fact is supported by several studies, which suggested that training and motivation would affect the improvement of employee performances, as in research by [5], [15], [17], [20], [24], [32], [36] . Based on the study upon prior research, either conceptually or empirically, a hypothesis was proposed as follows:…”
Section: The Effect Of Motivation On Performancementioning
confidence: 63%
“…It was found that ST can influence positively employees' organizational behavior (Kacmar et al, 2012), performance (Braun et al, 2013), and pay their attention to contribute greatly to the organization through extra-role performance (Lam, Loi and Leong, 2013). Also, TS has a positive on employees' work engagement (Chughtai, Byrne and Flood, 2015) which encourage the employees to share their knowledge to professionally perform their tasks (Silic and Back, 2017).…”
Section: Trust In Supervisor and Knowledge Sharingmentioning
confidence: 99%
“…A potential goal of Susman and Evered (1978) gamification is "serving a business purpose," and fulfilling a business purpose (Zichermann and Linder, 2013: p. 51). Because of the effectiveness of gamification on directing behavioral change (Matallaoui et al, 2015), it has received abundant attention from KM researchers in the last few years (Shpakova et al, 2017;Silic and Back, 2017;Suh and Wagner, 2017).…”
Section: Gamification Approachmentioning
confidence: 99%
“…The potential of gamification for motivating people to share their knowledge has been recognized by a growing amount of studies conducted in recent years (Kwon et al, 2015;Swacha, 2015;Silic and Back, 2017). The scientific literature mainly contains theoretical papers, but investigating the long-term effects of gamification in the context of corporate KM is still rare (Friedrich et al, 2019).…”
Section: Introductionmentioning
confidence: 99%